2005
DOI: 10.1007/s00134-005-2660-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of cocaine body-packers

Abstract: Good prognosis observed in these body-packers cases is due to the careful monitoring of asymptomatic patients, allowing early detection and treatment of complications. Surgical removal of the packets when complication occurs is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 21 publications
1
41
0
7
Order By: Relevance
“…McCarron and Wood7 identified three types of drug packets (see table 1). de Prost et al ,6 in a series of 581 body packers, found that type 1 packets were rare (prevalence 9%), but were strongly associated with complications, being present in five of the eight patients (prevalence 62.5%) who required admission to the intensive therapy unit for complications including poisoning and obstruction. A drug history may reveal drug dependence or co-ingestion of constipating agents to prevent premature passage of the deadly cargo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…McCarron and Wood7 identified three types of drug packets (see table 1). de Prost et al ,6 in a series of 581 body packers, found that type 1 packets were rare (prevalence 9%), but were strongly associated with complications, being present in five of the eight patients (prevalence 62.5%) who required admission to the intensive therapy unit for complications including poisoning and obstruction. A drug history may reveal drug dependence or co-ingestion of constipating agents to prevent premature passage of the deadly cargo.…”
Section: Resultsmentioning
confidence: 99%
“…Although there were no randomised trials, 10 case series were identified 1 412. Only two case series reported on more than 100 cases; 581 cocaine body packers in France6 and 572 suspected body packers in England 1. Numerous other single and double case reports were found in both the biomedical and forensic science literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…La distinción de estos dos escenarios determinará el manejo del paciente, bien sea conservador o quirúrgico 3,15 . El manejo de los que constituyen la mayoría de los "body packers", pacientes asintomáticos, actualmente se enfoca en la evacuación espontánea de los paquetes durante la monitorización y observación continua de signos vitales, previniendo las posibles complicaciones, dado por el enfoque interdisciplinario del servicio de Urgenciología, Toxicología y Cirugía general 16 . Aunque la cirugía temprana alguna vez fue recomendada en este tipo de pacientes, probablemente debido a la alta tasa de ruptura espontánea de los paquetes con envoltura primitiva 17 , con la realización de múltiples estudios sobre el manejo conservador desde los años ochenta se ha reportado una tasa de fracaso del manejo médico conservador del alrededor del 5 %, y puede ir en descenso en la medida que la producción de los paquetes mejora, como se evidenció en nuestro trabajo, con una tasa de éxito del 100 % con el uso de polietilenglicol (PEG) 4,[18][19][20][21] .…”
Section: Discussionunclassified
“…2 Immediate laparotomy is indicated in case of high suspicion of rupture. 2,3 There are relatively few in vivo data regarding the toxicokinetics of cocaine and its metabolites in body-packers who develop clinical symptoms and require surgical management. 4 We describe here a case with serial determination of plasma concentrations of cocaine and its metabolites.…”
Section: Introductionmentioning
confidence: 99%